Соль земли: роман / Г. М. Марков - Марков Георгий Мокеевич (Сибириада, 2012)
Экземпляры: (20220407) / Инвентарный номер: 36133 / Цена: 180.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: М 27 / ГРНТИ: 17 / ББК: 84(2=411.2)6